Assessment of Burden Among Family Caregivers of Schizophrenia: Psychometric Testing for Short-Form Zarit Burden Interviews - Yu, Yu; Liu, Zi-wei; Zhou, Wei; Chen, Xiao-chuan; Zhang, Xing-yu; Hu, Mi; Xiao, Shui-yuan (Frontiers in Psychology, 2018)
Objective: Although various short forms of Zarit Burden Interview (ZBI) have been developed, there is a lack of standard psychometric testing and comparison among them. The study aims to examine the psychometric properties of ten short versions of the most frequently used ZBI among a sample of schizophrenia caregivers and to find the one with the best performance. Methods: Cross-sectional door-to-door survey of ZBI-22 and a series of validated instrument data from 327 family caregivers of schizophrenia patients in a Chinese rural community were conducted from October 2015 to January 2016. Reliability was assessed using McDonald's omega coefficient (ω). Validity including concurrent validity, known group's validity, and criterion validity were assessed by Spearman correlations and Mann-Whitney U tests. Overall discrimination ability was evaluated using the area under the receiver operating characteristic curve (AUC). Results: Reliability was generally good for all short forms (ω = 0.69–0.84), except for the Gort ZBI-4 (ω = 0.58), which is acceptable considering its small item numbers. Concurrent validity was good across all various ZBI forms with significant negative correlations with patient's function (r = −0.34 to −0.48, p < 0.01), as well as significant positive correlations with caregiver's depression (r = 0.49–0.65, p < 0.01), and anxiety symptoms (r = 0.45–0.58, p < 0.01). Known groups' validity (carers with disease vs. without disease; carers being parents vs. spouse vs. others) showed inconsistent results among various short forms. Criterion validity was generally good for all short forms with significant positive correlations with Family Burden Interview Schedule (r = 0.67–0.75, p < 0.01), except for the Higginson ZBI-1(r = 0.57, p < 0.01). Discriminative ability was also good for all short forms (AUC range: 0.85–0.99), with various cutpoints proposed. Among all ten short forms, the Ballesteros ZBI-12 and the Gort ZBI-7 outperformed others with almost equally good performance in comprehensive psychometric testing. Conclusions: This study provides support for the reliability, validity, and discriminative ability of the ten various short forms of ZBI for use among schizophrenia family caregivers, with the Ballesteros ZBI-12 and the Gort ZBI-7 endorsed as the best ones.